Youth who neither work nor study: The Peruvian case - Málaga, Ramiro (2014)
Drawing on information from the Encuesta de la Transición de la Escuela al Trabajo 2012 (Survey on the Transition from School to Work), this study analyzes the characteristics of young people who are not in education, employment or training (NEETs). We find that, overall, 17.94% of Peruvian urban youth between 15 and 29 years of age are NEETs. Of these, around three quar- ters (74.09%) are females, which points toward the presence of factors associated with gender, such as fertility, the role within the household economy, or educational reasons, such as the explanatory variables in the previous result.Accordingly, the likelihood of being a NEET increases for females if there are children in the house- hold and if the individual has a partner, while the reverse is true in the case of males. Moreover, the likelihood of belonging to the NEET group increases when there are young men in the household; decreases when they are heads of household; if there is production in the household; or if the part- ner is engaged in domestic work. As regards individual decisions, young people’s life goals affect the likelihood of being a NEET. Moreover, the higher the level of education, the lower the likelihood of being a NEET due to the greater opportunity cost associated with better earning prospects.